Strategy for Cultural Tourism Development in Wajo District - Yahya, ‎; Nawawi, Juanda; Abdullah, Muh. Tang (KnE Social Sciences, 2025)
Cultural tourism development has great potential to enhance the economy and regional development, including in Wajo District. As a region rich in cultural potential and traditions, Wajo possesses various cultural heritage assets that can be utilized as tourist attractions. However, tourism development in Wajo still faces various challenges, such as a lack of integrated management, insufficient infrastructure, and limited promotion and marketing of the cultural tourism potential. Therefore, a proper strategy is needed to leverage the existing cultural potential as a driving force for tourism development in Wajo District. The strategy for cultural tourism development in Wajo District must consider sustainability, cultural preservation, and the empowerment of local communities. Cultural tourism development can create interesting and sustainable tourist destinations through an approach that involves all stakeholders, including the local government, community, and private sector. Several key steps that need to be considered in this strategy include the development of supporting infrastructure, improving human resources quality in tourism, building an effective marketing and promotion system, and strengthening cooperation between the government and the community in tourism management. In addition, to support the sustainability of cultural tourism development, it is necessary to involve the younger generation in maintaining and preserving local cultural traditions. Education and training programs focusing on cultural tourism can be an initial step in fostering awareness and enthusiasm to preserve the region’s cultural heritage. Therefore, cultural tourism development in Wajo District can provide optimal benefits in terms of economy, society, and culture.